More reliability of suspicious symptoms plus chest CT-scan than RT_PCR test for the diagnosis of COVID-19 in an 18-days-old neonate - Sepideh Mahdavi; Amirhessam Kheirieh; Salman Daliri; Mohammad Hossein Kalantar; Maryam Valikhani; Ahmad Khosravi; Mostafa Enayatrad; Mohammad Hassan Emamian; Reza Chaman; Marzieh Rohani-Rasaf (IDCases, 2020)
The present study investigated an 18-days-old neonate who was referred to the hospital with suspected respiratory symptoms of COVID-19. Results of CT-Scan and blood tests were highly suspicious, but result of the first RT-PCR test was negative on March 1. The second RT-PCR test reported positive on March 12. The neonate's medical history indicated no close contact except with family members and hospital treatment staffs, but the RT-PCR test results of all family members were also negative.